«The money that is never enough». Meanings and evaluations of monetary cash transfers during the pandemic (Estudios Sociales, 2024)
The aim of this paper is to analyze and reconstruct the assessments of different social profiles on the money that the national and provincial states implemented as an assistance policy during the health crisis unleashed by the COVID-19 virus. Through qualitative fieldwork carried out in the city of Santa Fe (and surrounding areas)-Argentina, where we reconstruct the household budgets of selected cases, we will analyze the strategies and repertoires of economic practices mobilized in households, paying attention to the presence of money transferred by the State as a specific monetary technology that penetrates, links, and assembles with diverse financial resources. This approach will allow us to problematize the interpretations produced by assisted households to evaluate state money, its scope, and limits.
Keywords: COVID; state money; assessments; well-being infrastructures